What is educación intercultural bilingüe in Latin America nowadays: results and challenges. Issue 10 (26th November 2021) - López, Luis Enrique
ABSTRACT: This article offers a critical appraisal of educación intercultural bilingüe, an educational model with at least five decades of implementation. When this term was coined, Indigenous populations were mostly monolingual and their settlements mostly rural and distant from the seats of cultural hegemony and power. The situation is now different; Indigenous individuals have also reached the centres of power, reclaiming their indigeneity. With these profound social, cultural and economic changes in mind, the evolution of EIB is examined to determine whether it still responds to the varying needs and expectations of Indigenous individuals, as well as to different sociolinguistic settings, since they may now be either passive or active bilinguals or even, increasingly, monolingual in the hegemonic language. We look at EIB through the lens of language ideology, policy and planning, and also through an educational one. Its main contributions to public policy vis-à-vis cultural and linguistic diversity are outlined and examined through a twofold perspective: a top-down one characterising official EIB, and a bottom-up one resulting from Indigenous agency. We close with an analysis of the challenges and possible new horizons for intercultural bilingual education and other Indigenous political-pedagogical undertakings.